Level of sexual and reproductive health knowledge and attitude among early adolescent - Abd. Aziz, Karimah Hanim; Jamani, Nurjasmine Aida; Lahasan, Nur Wajihah; Che Ujang, Syazwana Amira; Ali Hanafiah, Nur Ili Dalia (Kulliyyah (Faculty) of Medicine, International Islamic University Malaysia, 2018)
Topic on sexuality has largely remained a taboo subject for discussion between parents and their children in Malaysia, which might contributed to increase sexual activity among adolescent age group. This study was undertaken to assess the level of knowledge, attitude and their associated factors among standard 4 and 5 students in a primary school in Kuantan, Pahang.